Trouble along the way [videorecording (DVD)] - Cirtiz, Michael; Wayne, John, 1907-1979; Reed, Donna, 1921-1986; Jackson, Sherry, 1942- (John Wayne collection (Warner Bros.), 2007)
Struggling to retain custody of his daughter following his divorce, football coach Steve Williams finds himself embroiled in a recruiting scandal at the tiny Catholic college he is trying to bring back to football respectability.